Developing a definition of functional rural areas in the EU - Lewis Dijkstra; Chris Jacobs-Crisioni (European Commission, Joint Research Centre (JRC), 2023)
This paper develops a methodology to define functional rural areas in the EU. It seeks feedback on the method and the results. Functional rural areas cover all the territory outside functional urban areas. They are constructed in three steps. First, we define rural centres: they are the largest town or village within a 10-minute drive. Second, we create catchment areas by assigning every grid cell to the nearby rural centre that has the greatest gravitational pull. Third, we combine small and nearby catchment areas. We combine catchment area until each has at least 25 000 inhabitants or is more than an hour's drive away from the surrounding catchment areas. We also combine catchment areas that have centres that are less than a 30-minute drive apart, even if they have a population of at least 25 000 inhabitants. Next, we show that functional rural areas are more harmonised in terms of population and area size than LAUs and NUTS-3 regions. The analysis of population change and of the distance to the nearest school shows that the results by functional area are less volatile than the results per LAU and show more detail than the results per NUTS-3 regions. Functional rural areas can inform policies that promote access to services and that respond to demographic change. They can also be used to inform transport infrastructure investments and public transport provision.
Keywords: 330; Ländlicher Raum; Ländliche Entwicklung; Entwicklungsplanung; EU-Staaten